A Comparative Study Of Education In Nigeria and Niger: Challenges and Solutions - Usman Muhmmad Malah; Komarudin Sassi (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2024)
The topic deals with education in Nigeria and Niger, challenges and solutions, and aims to identify the challenges facing education in Africa in general and in Nigeria and Niger in particular, and the difficulties that students and pupils suffer from before, during and after school, and the impact of colonial countries on not developing education and learning, controlling the curricula and leaving an educational system that serves their interests, and the researcher follows the descriptive and analytical method, to reach The desired or expected results at the end of the research, and the expected results at the end of the research are, the presence of officials and experts who are interested in developing education in Nigeria and Niger, and the application of curricula on the ground, which helps the community to obtain a good education, and governments are expected to pay attention to public education and provide supplies for this, there is a lack of competencies of employees and experienced professors in government primary schools. Because education in Nigeria and Niger is similar, the difference in the language of education may be a result of colonization, in Niger it is French, and in Nigeria the official language is English, we take a look at some of the history of education in the two countries, and some challenges and solutions.